Influence of Cultivation Practice and Mowing Height on Conversion of Golf Course Rough from Tall Fescue to ‘Sharps Improved II’ Buffalograss - J. Reeves; J. Hoyle; D. Bremer; S. Keeley; J. Griffin (Kansas Agricultural Experiment Station Research Reports, 2015)
Slit-seeding buffalograss provided the quickest (85% cover, 8 weeks after seeding) establishment of all the cultivation practices. Mowing height had no effect on establishment success.
Keywords: turfgrass; cultivation; mowing height; tall fescue; ' Sharps Improved II' buffalograss; Buchloe dactyloides (Nutt.) Engelm; Schedonorus arundinaceus